Multi-target regulation of cellular senescence by traditional Chinese medicine: a novel strategy to preventing diabetic kidney disease - Chen Wang; Dongfeng Chen; Yonghui Yin; Xiujuan Liu; Yi Liu; Xiaoyun Li; Chang Kong; Quanlin Zhao (Renal Failure)
Diabetic kidney disease (DKD) is a common chronic microvascular complication of diabetes and the leading cause of end-stage renal disease. Its pathogenesis is closely linked to cellular senescence. Studies have shown that cellular senescence drives DKD progression via multiple mechanisms, including tubulointerstitial fibrosis, glomerulosclerosis, oxidative stress, and aberrant AMP-activated protein kinase (AMPK)/mammalian target of rapamycin (mTOR) signaling. However, there remains a lack of specific therapeutic targets or effective drugs for DKD treatment. Traditional Chinese medicine (TCM), characterized by its multidimensional, multi-target, significant efficacy, and fewer adverse effects, has shown unique advantages in DKD prevention and treatment. This article systematically examines the role of cellular senescence in DKD pathogenesis and, guided by TCM theory, explores how TCM may regulate cellular senescence to mitigate DKD, offering novel perspectives for enhancing clinical management of this condition.